Social and environmental conflicts or sustainable development? Positive alarmism - Hrubec, Marek (Civitas: revista de Ciências Sociais, 2019)
The article deals with the topic of mutually interlinked social and environmental conflicts and their possible resolution. First, it articulates the main ideas of the problematic historical dialectic of Western civilization. Second, it focuses on the whole human civilization as well. The sceptical explanatory critique of the historical and current development of the civilization(s) can be a contribution to, first, a positive alarmism which, second, can be reformulated by more developed and sophisticated contemporary analyses. Third, the article analyses a necessary transition from a monological paradigm to an intersubjective paradigm of relations among human beings and the nature in the contemporary context of global capitalism in order to overcome the problematic dialectic of the civilization(s). *** Conflitos socioambientais ou desenvolvimento sustentável? Alarmismo positivo *** O artigo trata do tema dos conflitos sociais e ambientais interligados entre si e de sua possível resolução. Em primeiro lugar, articula as principais ideias da problemática dialética histórica da civilização ocidental. Em segundo lugar, enfoca toda a civilização humana também. A crítica explicativa cética do desenvolvimento histórico e atual da(s) civilização(ões) pode ser uma contribuição para, em primeiro lugar, um alarmismo positivo que, segundo, pode ser reformulado por análises contemporâneas mais desenvolvidas e sofisticadas. Terceiro, o artigo analisa a necessária transição de um paradigma monológico para um paradigma intersubjetivo de relações entre seres humanos e a natureza no contexto contemporâneo do capitalismo global para superar a problemática dialética da(s) civilização(ões). Palavras-chave: Ambiente. Conflito ecológico. Conflito social. Alarmismo. Capitalismo global.